SUPERVISI MANAJERIAL DALAM PENINGKATAN MUTU FASILITAS DAN LINGKUNGAN BELAJAR DI PONDOK PESANTREN RAUDLOTUL MUTA'ALLIMIIN - Hilmiyatul Latifah; Hasyim Asy’ari; Sita Ratnaningsih (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study examines the implementation of managerial supervision in improving the quality of facilities and learning environments at the Madrasah Ibtidaiyah of Pondok Pesantren Raudlotul Muta’allimiin. The research focuses on how the Kiai’s value based vision is translated into supervisory practices, how administrative actors navigate structural constraints, and how students experience the impact of supervision. Using a qualitative approach with a single case study design, data were collected through in-depth interviews, participatory observations, and document analysis. The data were analyzed thematically through processes of reduction, presentation, and verification. The findings reveal three major themes. First, managerial supervision serves as a value translation process in which the Kiai’s spiritual vision particularly regarding cleanliness, discipline, and moral responsibility is transformed into daily supervisory procedures. Second, supervisory practices are challenged by structural limitations such as constrained budgets and delayed facility repairs, resulting in gaps between evaluation and follow-up actions. Third, supervision successfully fosters participatory resonance among students, marked by a shift from extrinsic compliance toward intrinsic responsibility in maintaining their learning environment. The study concludes that the quality of educational facilities in pesantren is shaped by the interplay of spiritual values, transformational leadership, and institutional capacity to act on supervisory findings. Effective managerial supervision, therefore, requires not only procedural accuracy but also sustained value alignment and resource readiness to ensure continuous improvement.